Developing the halal ecosystem in Indonesia through productive waqf: A development strategy from the Indonesian halal industry masterplan 2023-2029 - Muhammad Faiz Andeaz Fawwaz; Ayu Tri Nursyarah; Mursid Ash Shidiq; Dinda Tasya Putri Lubis (Halal Studies and Society, 2026)
The Indonesian halal industry is faced with significant structural challenges despite the country’s status as the world’s largest Muslim population and the implementation of the Indonesian Halal Industry Masterplan (MPIHI) 2023-2029. The key challenges include logistical inefficiencies, high investment costs for segregated supply chains, limited access to capital for micro, small, and medium enterprises (MSMEs), and a talent crisis in human resources. Therefore, this study aimed to evaluate the role of productive waqf on improving the halal ecosystem in Indonesia, using a qualitative method with content analysis. The results showed that productive waqf acts as patient capital, offering long-term, low-cost financing and physical infrastructure that commercial banking cannot provide. A Waqf-Based Industrial Clustering model and a Waqf-Blended Finance strategy were proposed to achieve economies of scale and absorb initial business risks, respectively. Furthermore, the study suggests reforming the role of Nazhir as managers from passive asset holders into professional Supply Chain Integrators. By integrating waqf assets into the national halal ecosystem, Indonesia reduced production costs, ensured halal integrity, and accelerated its vision of becoming a global halal production center.